Thin targets for nuclear reaction studies using NAND facility. (April 2018) - Mahajan, Ruchi; Abhilash, S.R.; Sharma, Priya; Kaur, Gurpreet; Kabiraj, D.; Duggal, Heena; Mehta, D.; Behera, B.R.
Abstract: Isotopic thin Samarium (Sm) targets of 150–200 μg/cm 2 thickness have been fabricated in high vacuum (HV) environment by thermal evaporation method on carbon (C) backing of 20–25 μg/cm 2 thickness at Inter University Accelerator Centre (IUAC), New Delhi. Salient features of the method used for fabrication of 144, 154 Sm targets are enumerated below:   A very thin layer of C of thickness 5–10 μg/cm 2 has been evaporated on Sm using electron-gun bombardment technique.   The detailed fabrication procedure along with various challenges faced (peeling off, oxidizing nature of the target etc.) has been discussed in this article.   Energy dispersive X-ray fluorescence (EDXRF) has been used to access the purity, thickness and elemental composition of targets. There is no trace of high Z impurity present in the prepared targets.   These targets have been successfully used in three nuclear physics experiments using the National Array of Neutron Detectors (NAND), HYbrid Recoil Mass Analyzer (HYRA) and General Purpose Scattering chamber (GPSC) at IUAC, New Delhi. Highlights: Very thin (150–200 μg/cm 2 ) targets of enriched 144, 154 Sm has been prepared using thermal evaporation method. A flash of carbon topping was done in order to avoid the oxidation of the targets. These targets have been used for nuclear reaction studies at near and above Coulomb barrier energies.